2022
DOI: 10.1002/path.5970
|View full text |Cite
|
Sign up to set email alerts
|

Absence of NOTCH1 mutation and presence of CDKN2A deletion predict progression of esophageal lesions

Abstract: Currently, surveillance for esophageal squamous cell carcinoma (ESCC) runs a risk of underestimation of early lesions which show absence of iodine staining, with no or only mild histologic changes. The development of molecular markers that indicate risk of progression is thus warranted. We performed whole‐exome sequencing on biopsies from two sequential endoscopies of a single esophageal lesion and matching blood samples. There were 27 pairs of age‐, gender‐, pathologic stage‐, and sampling interval‐matched pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Significant differences in the mutation frequencies of NOTCH1 and NOTCH2 (more frequent in PNM than in ESCC); copy number variations at both the gene and chromosomal arm level; and mutations in cancer-related HIPPO, WNT and NRF2 signaling pathways (more frequent in ESCC than in PNM) were observed. Importantly, the frequencies of TP53 gene mutations were higher in PNM derived from ESCC cases compared with those observed in PNM derived from gastric cancer patients [12].…”
Section: Precursor Lesions Of Esccmentioning
confidence: 77%
See 1 more Smart Citation
“…Significant differences in the mutation frequencies of NOTCH1 and NOTCH2 (more frequent in PNM than in ESCC); copy number variations at both the gene and chromosomal arm level; and mutations in cancer-related HIPPO, WNT and NRF2 signaling pathways (more frequent in ESCC than in PNM) were observed. Importantly, the frequencies of TP53 gene mutations were higher in PNM derived from ESCC cases compared with those observed in PNM derived from gastric cancer patients [12].…”
Section: Precursor Lesions Of Esccmentioning
confidence: 77%
“…In 11 patients, Liang et al evaluated the genome profiles using whole-exome sequencing in physiologically normal mucosa (PNM), ESCC cancer tissue and PMN samples from non-ESCC gastric cancer [12]. Significant differences in the mutation frequencies of NOTCH1 and NOTCH2 (more frequent in PNM than in ESCC); copy number variations at both the gene and chromosomal arm level; and mutations in cancer-related HIPPO, WNT and NRF2 signaling pathways (more frequent in ESCC than in PNM) were observed.…”
Section: Precursor Lesions Of Esccmentioning
confidence: 99%
“…Liu and his colleagues demonstrated that the presence of CDKN2A deletion might induce the progression of ESCC. [ 39 ] In T-cell acute lymphoblastic leukemia, CDKN2A deletion was an independent poor prognostic factor. [ 40 ] Similar to the above findings, deep deletion happened in most cancer types.…”
Section: Discussionmentioning
confidence: 99%